ANALISIS FAKTOR YANG MEMPENGARUHI LOYALITAS KONSUMEN TERHADAP PRODUK LOKAL - Hendra Pasu Parningotan Simanjuntak (Fakultas Teknologi dan Rekayasa, 2017)
The purpose of research is to analyze the customers to factors influencing theloyalty of local produce water carelessly in packs Aquanab Nabire. The research isresearch survey. Total sampel off 100 respondents who set with a method of clusters of thesampling method of and as the discussion was the cluster 3 district in Nabire Regencywho was determined randomly. Data analysis used the method Structural EquationModelling (SEM).Based on the result of research from analysis of it can be concluded that isgetting strongger commitment, trust, the involvement, communication by word of mouth,proximity products and customer satisfaction will result in intention to buy back the morepowerful. Satisfaction customers dont mediate the influence of a commitment to intentionto buy back water carelesly in packs, but mediate the customer satisfaction in theinfluence of trust, the involvement, communication by word of mouth.